Efficacy of combined antiparasitic therapy with praziquantel and albendazole for neurocysticercosis: a double-blind, randomised controlled trial - Garcia, Hector H (2014)
BACKGROUND: Neurocysticercosis causes a substantial burden of seizure disorders worldwide. Treatment with either praziquantel or albendazole has suboptimum efficacy. We aimed to establish whether combination of these drugs would increase cysticidal efficacy and whether complete cyst resolution results in fewer seizures. We added an increased dose albendazole group to establish a potential effect of increased albendazole concentrations. METHODS: In this double-blind, placebo-controlled, phase 3 trial, patients with viable intraparenchymal neurocysticercosis were randomly assigned to receive 10 days of combined albendazole (15 mg/kg per day) plus praziquantel (50 mg/kg per day), standard albendazole (15 mg/kg per day), or increased dose albendazole (22·5 mg/kg per day). Randomisation was done with a computer generated schedule balanced within four strata based on number of cysts and concomitant antiepileptic drug. Patients and investigators were masked to group assignment. The primary outcome was complete cyst resolution on 6-month MRI. Enrolment was stopped after interim analysis because of parasiticidal superiority of one treatment group. Analysis excluded patients lost to follow-up before the 6-month MRI. This trial is registered with ClinicalTrials.gov, number NCT00441285. FINDINGS: Between March 3, 2010 and Nov 14, 2011, 124 patients were randomly assigned to study groups (41 to receive combined albendazole plus praziquantel [39 analysed], 43 standard albendazole [41 analysed], and 40 increased albendazole [38 analysed]). 25 (64%) of 39 patients in the combined treatment group had complete resolution of brain cysts compared with 15 (37%) of 41 patients in the standard albendazole group (rate ratio [RR] 1·75, 95% CI 1·10–2·79, p=0·014). 20 (53%) of 38 patients in the increased albendazole group had complete cyst resolution at 6-month MRI compared with 15 (37%) of 41 patients in the standard albendazole group (RR 1·44, 95% CI 0·87–2·38, p=0·151). No significant differences in adverse events were reported between treatment groups (18 in combined treatment group, 11 in standard albendazole group, and 19 in increased albendazole group). INTERPRETATION: Combination of albendazole plus praziquantel increases the parasiticidal effect in patients with multiple brain cysticercosis cysts without increased side-effects. A more efficacious parasiticidal regime without increased treatment-associated side-effects should improve the treatment and long term prognosis of patients with neurocysticercosis. FUNDING: National Institute of Neurological Disorders and Stroke (NINDS), National Institutes of Health.